A model of user acceptance of learning management systems : a study within tertiary institutions in New Zealand : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Information Systems at Massey University, New Zealand - Nanayakkara, Charith (Massey University, 2006)
Digital technologies are revolutionizing the practices of teaching and learning at colleges and universities all around the world. With the emergence of internet and web technologies, tertiary institutions are increasingly exploring the potential use of e-learning technologies to cater for the ever growing demands of flexible teaching needs in distance education. The teaching institutions are making significant efforts in e-learning development and investing significantly in associated information technology infrastructure with the expectation of high return on their investment. However, in spite of this effort and investment the teachers and faculty do not always use the technology as expected and more often e-learning systems continue to be underutilised. This research investigates the factors that influence or inhibit the adoption of e-learning systems in the universities, institutes of technology and polytechnics in New Zealand. A cross section of teaching staff from different tertiary institutions was surveyed to ascertain their views on adopting learning management systems (LMS) in their teaching process. The survey questionnaire is based on factors that are being advocated by well known practitioners and academics, which were identified through a literature review. The study reveals three key groups of factors: individual, system and organisational, affecting the adoption of e-learning systems in the tertiary institutions. The report introduces a theoretical framework for user acceptance of e-learning systems and presents a detailed analysis for factors relating to: (a) individual characteristics (b) individual perceptions (c) LMS system characteristics (d) external system characteristics (e) organisational support and (f) organisational characteristics. The results show that whilst individual factors have significant contribution to the LMS adoption, the system and organisational factors are most crucial for user acceptance in e-learning systems. The users ranked that release time for staff, the ease of use of LMS, perceived usefulness of LMS, training and support to develop online content and the reliability of information and communication technology infrastructure are the five most essential factors for staff uptake in e-learning systems.
Keywords: New Zealand Higher Education; Computer-assisted instruction; Internet in higher education